Literasi Digital dalam Dunia Pendidikan di Era Revolusi Society 5.0 Termasuk Pemanfataan ICT pada Pendidikan - Siti Nurjanah, Dita; Dewi Masithoh, Ucik; Zulfaidah, RA. (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2024)
In the era of the revolution of society 5.0, digital literacy and ICT (Information and Communication Technologies) or better known as information and communication technology play an important role in the world of education. Digital literacy is the user's knowledge and skills in dealing with digital media such as social media and the internet. Digital competence is an inseparable part of knowledge. Currently, information is not only in the form of newspapers, magazines, and others, but can also be obtained through digital media. This study aims to determine the use of digital literacy and ICT in education. This research is included in the category of qualitative research using library research. The results obtained from this study indicate that digital literacy and ICT are very useful in the world of education and are inseparable because ICT is a means of accessing digital literacy. Currently, the government is focusing on the National Literacy Movement (GPL) which includes 8 sections to develop digital literacy, including cultural, cognitive, constructive, communicative, assertive, responsible, critical and social elements. The use of digital literacy in the world of education in the 5.0 era also includes the use of ICT in education, which consists of using e-education, learning management systems, virtual laboratories, online repositories, ebooks, ejournals, online encyclopedias and contained in an article that we have compiled.